PENGARUH KUALITAS PRODUK, HARGA, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PELANGGAN TUPPERWARE DI IIK BHAKTI WIYATA KEDIRI) - Rahajeng Sulistyaningtyas; Abu Talkah; Edy Swasono (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
In the future now, world environment business experienced various changes which have so fast in the mark with the free trade and expansion science and technology more advanced. The changes characterized by the development of science and technology more advanced by the presence of the development of very rapidly company are required to create new innovations can be found in a variety of products. Companies are required to more attention to factors factors like quality products, prices and a promotion company did to take sympathy consumers to do decision the purchase of that product. This study aims to to analyze the influence of quality products, prices and promotion of the decision the purchase (study in customers tupperware products in iik bhakti wiyata kediri). Collection method to research was conducted by using a questionnaire. Research population is the customer tupperware products on employees iik bhakti wiyata kediri, with the total sample 98 those on take with both slovin method. The technique the sample used in this research was incidental sampling where the sample done by chance met with the can be used as samples. Analysis techniques the data used analytics multiple regression previously tested assuming classic. This research result indicates that the variable quality of the product higher compared with variable price and promotion. This means the quality of the product most dominant compared prices and promotion of the decision of the purchase. Partial evaluation and simultaneous there is the influence of a positive and significant between the quality of products, the price of, promotion of the decision of the purchase of tupperware.